A Dictionary of Landscape : a dictionary of terms used in the description of the world's land surface - Goulty, George A. (Avebury Technical, 1991)
"This dictionary is an essential work of reference for all persons working in the land use professions, students and the general public who need to know the meaning of a technical term or current jargon. Lik all other branches of the art and sciences, as knowledge increases so the vocabulary expands to keep pace with new ideas. Some words in common usage are adopted to express these new concepts, whilst in other cases new words are created. In both instances the thoughtless author and unsuspecting reader may easily be misled by such words used in a special technical sense. This dictionary is intended to eliminate this risk in respect of words concerned with describing landscape forms, land uses and vegetative cover worldwide. The dictionary runs to 309 pages and contains over three thousand entries." --Back Cover.